Breaking bud dormancy and different shade levels for production of pot and cut Cucurma alismatifolia - Abdullah, Thohirah Lee; Chin, Flora Lee Sa; N., Kamalakshi (Science Publications, 2010)
Problem statement: Cucurma alismatifolia is a member of the family Zingiberaceae. It is widely grown in Thailand and is also a highly demanded plant in Holland and Israel where it is grown for cut flowers and as pot plants. C. alismatifolia has a good potential as a new flowering crop in the floriculture industry. The development of new flowering pot plants is of interest to commercial growers, nurserymen as well as hobbyists. Noted for its showy inflorescence and unique foliage, this plant is long lasting and durable. It is an herbaceous with short fleshy rhizomes and tuberous roots, often with a dormancy period. Breaking of the bud dormancy on the rhizomes of C. alismatifolia is very important as to overcome the problem of eye bud emergence and to provide planting material throughout the year. There is little information on the optimum production environment and cultivation practices of this species. Approach: This study reported on the study of plant morphology, the effects of BAP and ethephon in breaking bud dormancy of C. alismatifolia and the effects of different shade levels on the growth and flowering of C. alismatifolia. Results: BAP at 100 mg L-1 recorded the most number of eye buds appearance while ethephon at 750 mg L-1 gave the most number of eye emergence. Data obtained shown that the optimum shade level for the production of C. alismatifolia potted plant was at 30%. Conclusion: For commercial production of C. alismatifolia as a cut flower, a shade level of 70% is highly recommended, as it exhibits a good characteristic for a cut flower at this shade level.